SERVICE TAX COMPLIANCE IN MALAYSIA: A PROPOSED OF CONCEPTUAL FRAMEWORK - Maryani Jamian; Zainol Bidin; Saliza Abdul Aziz (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Service tax stands out as the primary revenue generator within Malaysia’s system of indirect taxation, emphasizing its crucial role in the country’s fiscal structure. However, research on service tax is relatively sparse compared to studies focused on direct taxes like income and corporate taxes. This discrepancy highlights a need for more comprehensive exploration into service tax dynamics. The objectives of this study are to propose a service tax compliance framework and to develop that framework by focusing on three independent variables: tax fairness, peer influence, and tax complexity. Additionally, trust is introduced as a moderating variable that could affect how these factors relate to tax compliant behaviour. This study utilizes Fisher’s model to analyse compliance behaviours. Additionally, trust in government was incorporated from the Slippery Slope Framework to enhance understanding of the dynamics involved in adhering to tax obligations. This study expected to make a significant academic contribution due to the limited existing literature on inquiries into indirect taxes. Moreover, look forward to offer insights compelling enough to drive policy making and strategies that enhance compliance rates among taxpayers throughout Malaysian territories.